tRNA derived fragments:A novel player in gene regulation and applications in cancer - Zhang, Shuangshuang; Yu, Xiuchong; Xie, Yaoyao; Ye, Guoliang; Guo, Junming (Frontiers in Oncology, 2023)
The heterogeneous species of tRNA-derived fragments (tRFs) with specific biological functions was recently identified. Distinct roles of tRFs in tumor development and viral infection, mediated through transcriptional and post-transcriptional regulation, has been demonstrated. In this review, we briefly summarize the current literatures on the classification of tRFs and the effects of tRNA modification on tRF biogenesis. Moreover, we highlight the tRF repertoire of biological roles such as gene silencing, and regulation of translation, cell apoptosis, and epigenetics. We also summarize the biological roles of various tRFs in cancer development and viral infection, their potential value as diagnostic and prognostic biomarkers for different types of cancers, and their potential use in cancer therapy.